If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 = 7x + 19 Reorder the terms: 7 + 5x = 7x + 19 Reorder the terms: 7 + 5x = 19 + 7x Solving 7 + 5x = 19 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 7 + 5x + -7x = 19 + 7x + -7x Combine like terms: 5x + -7x = -2x 7 + -2x = 19 + 7x + -7x Combine like terms: 7x + -7x = 0 7 + -2x = 19 + 0 7 + -2x = 19 Add '-7' to each side of the equation. 7 + -7 + -2x = 19 + -7 Combine like terms: 7 + -7 = 0 0 + -2x = 19 + -7 -2x = 19 + -7 Combine like terms: 19 + -7 = 12 -2x = 12 Divide each side by '-2'. x = -6 Simplifying x = -6
| 4x(8+x)= | | (7-u)(3u+2)=0 | | 5(3-2x)+4x=3(3x-1)+7 | | (5ab-7b+9a)+(3a-2b+4ab)= | | 5x-23=3x-7 | | 4x+4=x+7 | | 8-16x-6-5x=5 | | 12-x-2=3+4x+5 | | 2x+7-x=3+x+4 | | T(r+s)= | | T(t+s)= | | 4y=8y-45 | | 8.35b=9.2+5.28b | | 5(2x-7)=155 | | -3x+1=-9 | | 8w(4b+p)= | | -4=7w | | 4x*12=180 | | 7x+7-4(x+1)=6x+5 | | 2(x+2)=4x+1-2x | | 9x+3=-8+5x+19 | | 0.6(8x+16)=1.6-(x+2) | | 4p-6+6p=4 | | -12-5u=-48 | | 19x-4-.75x= | | -x/6=2/9 | | 2x-4+4+2x= | | 5a+10=0 | | 2x+28-x-1=34 | | 63=5(8k-5)-2(7k+8) | | 2x-4+4+4+2x= | | 19x-4-34x= |